1996
DOI: 10.1002/(sici)1097-4644(19961215)63:4<432::aid-jcb5>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Fluid shear stress induces actin polymerization in human neutrophils

Abstract: We have previously reported that a physiological range of shear stress induces neutrophil homotypic aggregation mediated by lymphocyte function-associated antigen-1 (LFA-1) and intercellular adhesion molecule-3 (ICAM-3) interactions. To further characterized the homotypic aggregation, actin polymerization was investigated in neutrophils stimulated by shear stress in comparison with formyl-methionyl-leucyl-phenylalanine (fMLP). In fMLP-stimulated neutrophils, actin polymerization was localized in the pseudopods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Moreover, the organization and structure of cytoskeletal components, such as actin, can also be modified by shear stress. 73 Other studies demonstrated differences in adhesive properties of platelets between static and dynamic conditions. 74 In a previous study we have also shown similar differences for tumor cells adhesion to ECM components.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the organization and structure of cytoskeletal components, such as actin, can also be modified by shear stress. 73 Other studies demonstrated differences in adhesive properties of platelets between static and dynamic conditions. 74 In a previous study we have also shown similar differences for tumor cells adhesion to ECM components.…”
Section: Discussionmentioning
confidence: 99%
“…This shear stress-induced actin polymerization is not observed when neutrophils are treated with anti-CD11a/CD18 or anti-ICAM-3 antibodies. In contrast, in fMLP-stimulated neutrophils actin polymerization in pseudopods is not mediated by a rise of cytosolic intracellular Ca 2++ (Okuyama et al, 1996).…”
Section: Membrane Integrin Distribution Under Fluid Shear Stressmentioning
confidence: 83%
“…It has been revealed that the TMCs showed increased stress fibers in response to mechanical stimulation such as cyclic mechanical stretch ( Duffy and O’reilly, 2018 ). For other cell types, the F-actin formation had also been shown to correlate closely with the shear stress ( Okuyama et al, 1996 ; Schleicher et al, 2008 ; Mu et al, 2015 ), depending on the mode and intensity of shearing ( Chen et al, 2004 ). The dynamic regulation of F-actin polymerization of TMCs in response to the shear stress may be significant for the maintenance of outflow resistance and IOP homeostasis.…”
Section: Conclusion and Discussionmentioning
confidence: 99%